Financial market regulation, country governance, and bank efficiency: Evidence from East Asian countries - Sok-Gee Chan; Mohd Zaini Abd Karim (Contemporary Economics, 2016)
This paper examines the relationship between financial market regulation, country governance and efficiency of commercial banks in East Asian economies during the period 2001-2008 using a two-stage estimation technique. In the first stage, we employ a non-parametric approach-Data Envelopment Analysis (DEA)-to estimate the banks' cost and profit efficiency scores and then Tobit estimation to analyze the impact of financial market regulations and country governance on bank efficiency. The results suggest that commercial banks in East Asia are relatively profit efficient rather than cost efficient. The findings show that countries with more financial freedom and independence are more cost efficient. Moreover, government effectiveness is found to be positively related to bank efficiency. Consistent with economic theory, corruption is negatively related to bank efficiency. Therefore, this study reveals the importance of financial market regulations and country governance as catalysts for efficient banking operations in East Asian economies.
Keywords: G21; G28; D24; 330; bank efficiency; institutional environment; data envelopment analysis; tobit regression; East Asia